(untitled) (Journal of Engineering, 2009)
Thermal pollution occurs when heated wastewater is discharged into rivers, lakes, oceans, or other water bodies. This will raise the temperature of the water body above its normal level and, consequently, will harm the aquatic live. Thermal Pollution problems will intensify as electricity usage increases unless substantial changes are made in the mode of discharge of the heated water. This paper is aimed to study the effects of heated water released from South-Baghdad Power Station on the water quality of Tigris River. Many parameters are test such as: Temperature (T), Total suspended solids (TSS), Total Dissolved Solids (TDS), Electrical Conductivity (EC), Hydrogen Ion (pH) and the dissolved oxygen (DO). Other parameters are tested to describe the heated water components such as Biochemical Oxygen Demand (BOD), Oil+Grease, and PO4.These parameters are compared with the allowable limits of rivers according to the Iraqi standards NO.25/1967 and found that some parameters exceed the allowable limits